Lepus othus Merriam 1900 - Don E. Wilson; Thomas E. Lacher, Jr; Russell A. Mittermeier (Lynx Edicions, 2016)
58. Alaskan Hare Lepus othus French: Lievre d / Alaska / German: Alaska-Hase / Spanish: Liebre de Alaska Other common names: Alaska Arctic Hare, Alaska Peninsula Hare, Alaska Tundra Hare, St. Michael's Hare, Tundra Hare, Swift Hare Taxonomy. Lepus othus Merriam, 1900, “St. Michaels, [Norton Sound], Alaska,” USA. Formerly, the three arctic species, L. timidus, L. arcticus, and L. othus, were included in L. timidus based on morphological characteristics that, relative to their distributions, form a circumpolar “ring species.” This is also supported by genetic analysis of mtDNA, although evidence based only on mtDNA should be treated cautiously. There is also the view that two species exist: L. timidus in the Old World and L. arcticus in Greenland, northern Canada, Alaska, and the Chukchi Peninsula, Russia. Other lagomorph taxonomists consider that L. arcticus is conspecific with L. timidus and distinct from L. othus. Until conclusive evidence is available, the three species are considered to be distinct with L. timidus in the Old World, L. othus in Alaska, and L. arcticus in northern Canada and Greenland. Nevertheless, the border between L. timidus and L. othus is not clear and might be either in the Bering Strait or in the Kolyma region, Russia. Recent molecular phylogenetic study suggests that the break occurs in the Bering Strait, but more studies are required for a conclusive demarcation because the study was only based on mtDNA. If the distribution includes eastern Siberian tschuktschorum it has priority over othus. Recent molecular phylogenetic studies suggest that the eastern Siberian population is more closely related to L. timidus, and L. othus is distinct from L. arcticus, but more studies are required for a conclusive distinction because the study was only based on mtDNA. Morphological studies found that L. othusis closer to L. townsendii than to other northern species of Lepus. Lepus othusis partially sympatric with L. americanus in Alaska. As taxonomists are still trying to clarify the species ...